Separação de misturas líquidas em escoamento pelicular por meio de radiação térmica - Guimarães, Laurinda Fátima da Fonseca Pereira (1985)
A model is proposed for the separation of twocomponent l iquid mixtures by way of change of phase. One of the components vaporizes at the surface of a liquid film that flows over a heated inclined plate. The vapor condenses in contact with a cold plate, parallel to and on top of the first one, fornling also a liquid film. In the maciel are analysed a) the process of heat transfer through the films and the change of phase, as first proposed by Nusselt; b) the process of radiation heat transfer, considering re-radiation effects and convective lasses. The relation between the two process is made by dimensionless groups, which represent thermal resistances and the energy mass influx on the system. The condensate mass flux, the increase on themass fraction of the non-volatile solute and temperatures are calculated as function of the groups previously mencioned and the geometry of the system.